Understanding ethnographic texts - Atkinson, Paul, 1947- (Newbury Park, Calif. ; London : SAGE, 1992)
Paul Atkinson presents useful advice on how to read, and therefore how to write, ethnography. He examines how ethnographers create field notes and how they do interview transcriptions, inevitably revealing the author's hand. He outlines various literary conventions used in ethnographic writing.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Ethnology -- Authorship; Ethnology -- Methodology